Inflammation both increases and causes resistance to FGF23 in normal and uremic rats. (3rd January 2020) - Rodríguez-Ortiz, Maria E.; Díaz-Tocados, Juan M.; Muñoz-Castañeda, Juan R.; Herencia, Carmen; Pineda, Carmen; Martínez-Moreno, Julio M.; Montes de Oca, Addy; López-Baltanás, Rodrigo; Alcalá-Díaz, Juan; Ortiz, Alberto; Aguilera-Tejero, Escolástico; Felsenfeld, Arnold; et al.
Abstract: Fibroblast growth factor 23 (FGF23) increases phosphorus excretion and decreases calcitriol (1, 25(OH)2 D) levels. FGF23 increases from early stages of renal failure. We evaluated whether strict control of phosphorus intake in renal failure prevents the increase in FGF23 and to what extent inflammation impairs regulation of FGF23. The study was performed in 5/6 nephrectomized (Nx) Wistar rats fed diets containing 0.2–1.2% phosphorus for 3 or 15 days. FGF23 levels significantly increased in all Nx groups in the short-term (3-day) experiment. However, at 15 days, FGF23 increased in all Nx rats except in those fed 0.2% phosphorus. In a second experiment, Nx rats fed low phosphorus diets (0.2 and 0.4%) for 15 days received daily intraperitoneal lipopolysaccharide (LPS) injections to induce inflammation. In these rats, FGF23 increased despite the low phosphorus diets. Thus, higher FGF23 levels were needed to maintain phosphaturia and normal serum phosphorus values. Renal Klotho expression was preserved in Nx rats on a 0.2% phosphorus diet, reduced on a 0.4% phosphorus diet, and markedly reduced in Nx rats receiving LPS. In ex vivo experiments, high phosphorus and LPS increased nuclear β-catenin and p65-NFκB and decreased Klotho. Inhibition of inflammation and Wnt signaling activation resulted in decreased FGF23 levels and increased renal Klotho. In conclusion, strict control of phosphorus intake prevented the increase in FGF23 in renal failure, whereas inflammation independently increased FGF23 values. Decreased Klotho may explain the renal resistance to FGF23 in inflammation. These effects are likely mediated by the activation of NFkB and Wnt/β-catenin signaling.